Motion processing impaired by transient spatial attention: Potential implications for the magnocellular pathway. (October 2022) - Pavan, Andrea; Koc Yilmaz, Seyma; Kafaligonul, Hulusi; Battaglini, Luca; Blurton, Steven P.
Highlights: Transient attention interferes with temporal segregation. Transient attention impairs the perception of real motion inhibiting the M system. Criterion shifts due to transient attention were negligible. Perceptual processing was initially faster for stimuli that were validly cued. Overall, neutrally cued targets were processed more efficiently. Abstract: Spatial cues presented prior to the presentation of a static stimulus usually improve its perception. However, previous research has also shown that transient exogenous cues to direct spatial attention to the location of a forthcoming stimulus can lead to reduced performance. In the present study, we investigated the effects of transient exogenous cues on the perception of briefly presented drifting Gabor patches. The spatial and temporal frequencies of the drifting Gabors were chosen to mainly engage the magnocellular pathway. We found better performance in the motion direction discrimination task when neutral cues were presented before the drifting target compared to a valid spatial cue. The behavioral results support the hypothesis that transient attention prolongs the internal response to the attended stimulus, thus reducing the temporal segregation of visual events. These results were complemented by applying a recently developed model for perceptual decisions to rule out a speed-accuracy trade-off and to further assess cueing effects on visual performance. In a model-based assessment, we found that valid cues initially enhanced processing but overall resulted in less efficient processing compared to neutral cues, possibly caused by reduced temporal segregation of visual events.